Hippasteria phrygiana Parelius 1768 ... - Mah, Christopher L. (Zenodo, 2011)
Hippasteria phrygiana (Parelius, 1768) (Figure 11 A–D) Linck, 1733: 21(as Pentaceros planus) Parelius, 1768: 425 [1770: 349] (as Asterias phrygiana) Lamarck, 1816: 555 [non A. equestris Retzius, 1805] (as Asterias equestris) Gray in Johnston, 1836: 146 (as Asterias johnstoni) Gray, 1840: 279, 1866: 9 (as Hippasteria europaea, H. johnstoni, H. cornuta) Gray, 1840: 279; 1866: 9; Perrier, 1875: 270 [1876: 65], Danielssen & Koren, 1881: 268; Sladen 1883: 159; Perrier, 1888: 764; Sladen, 1889: 341; Koehler, 1909: 88, 1924: 179 (as Hippasteria plana) Forbes, 1841: 125 (as Goniaster equestris) Müller & Troschel, 1842: 52; Duben & Koren, 1846: 246 (as Astrogonium phrygianum) Forbes, 1843: 280 (as Goniaster abbensis) Barrett, 1857: 47 (as Astrogonium aculeatum) Norman, 1865: 128 (as Goniaster phrygiana) Dons, 1938: 17 (as Hippasteria [Euhippasteria] phrygiana and Hippasteria [Nehippasteria] insignis) Perrier, 1891: K128; A.M., Clark 1962: 22; Koehler, 1926: 107; Bernasconi, 1963: 16; Codoceo & ... : Published as part of Mah, Christopher L., 2011, Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa, pp. 1-48 in Zootaxa 2759 on pages 27-30, DOI: 10.5281/zenodo.276783 ...